INNOVATIVE ANTIHYPERTENSIVE THERAPY IN THE LIGHT OF COMPLETED CLINICAL TRIALS - N. A. Nikolaev (Рациональная фармакотерапия в кардиологии)
The innovative approaches to antihypertensive pharmacotherapy and advantages of modern antihypertensive drugs are discussed on the basis of randomized controlled trial. The recommendations for usage of different class of antihypertensive drugs including their combinations are presented.